Determination of Endogenous Bufalin in Serum of Patients With Hepatocellular Carcinoma Based on HPLC-MS/MS - Han, Mengfei; Yang, Geliang; Lin, Qing; Yang, Yanlong; Zhang, Huiqing; Su, Yonghua (Frontiers in Oncology, 2020)
Bufalin is a cardiotonic steroid and a key active ingredient of the Chinese medicine ChanSu. It has significant anti-tumor activity against many malignancies, including hepatocellular carcinoma (HCC). Previous studies have shown that human bodies contain an endogenous bufalin-like substance. This study aimed to confirm whether the endogenous bufalin-like substances is bufalin and further detect the differences between HCC and control groups of endogenous bufalin concentration by the high-performance liquid chromatography coupled tandem mass spectrometry (HPLC-MS/MS). The results confirmed the endogenous bufalin-like substance is bufalin. Totally, 227 serum samples were collected: 54 from HCC patients and 173 from healthy volunteers constituting a control group. Both the test group and the control group contained bufalin in serum, revealing that bufalin is indeed an endogenous substance. The bufalin concentration was 1.3nM in HCC patients and 5.7nM in normal people（p<0.0001）. These results indicate that human bodies contain endogenous bufalin, and it may be negatively correlated with the incidence of HCC.